Optimising the national strategy for progressive employment absorption to ensure the rights and responsibilities of citizens in Indonesia - Ardyati, Rizda; Ikrimah, Afridah (Universitas Negeri Yogyakarta, 2025)
<!– ####### THIS IS A COMMENT - Visible only in the source editor #########–><p style=